2018
DOI: 10.3389/fpubh.2017.00362
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Impact of Cardiopulmonary Resuscitation Training on High School Students

Abstract: BackgroundThe American Heart Association (AHA) has implemented several programs to educate the public about cardiopulmonary resuscitation (CPR). A common issue in bystander CPR is the fear of hurting the victim. As a result, the victim may not receive CPR in time. The purpose of this study was to measure the emotional impact of CPR training on high school students using two approved AHA courses.MethodsA total of 60 students participated in this study. These students had a mean age of 15.4 ± 1.2 years old and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…The use of paediatric manikins to introduce and teach CPR to younger children will likely increase confidence during CPR training by providing positive feedback and increasing the positive emotional response to the training and learning (Abelsson et al, 2020; Alismail et al, 2018). It has previously been reported that schoolchildren believe they can save lives following Basic Life Support training.…”
Section: Discussionmentioning
confidence: 99%
“…The use of paediatric manikins to introduce and teach CPR to younger children will likely increase confidence during CPR training by providing positive feedback and increasing the positive emotional response to the training and learning (Abelsson et al, 2020; Alismail et al, 2018). It has previously been reported that schoolchildren believe they can save lives following Basic Life Support training.…”
Section: Discussionmentioning
confidence: 99%
“…Emotion has a substantial in uence on the cognitive processes including perception, attention, learning, memory and reasoning (24) . A study in teenagers showed that attending BLS training had a signi cant improvement in positive emotional scores (25) . While there is no comparable evidence for adult NHS staff attending BLS training, there may be a similar opportunity to create a positive environment to learn about organ donation.…”
Section: Introductionmentioning
confidence: 99%
“…6 Experience on BLS training influences high school students' willingness to perform BLS. 7 BLS knowledge influences college students' willingness to implement BLS. 8 Thus, interest, knowledge, and experience were involved in the willingness to implement BLS.…”
mentioning
confidence: 99%